Conversation Strategies Used By Students Of The English Department Of Tadulako University - Baso Andi Pallawa (Universitas Negeri Malang, 2014)
Conversation strategies are investigated based on two reasons. Firstly, many English stu-dents of the English Department of Tadulako University cannot actively participate in English conver-sation because they do know how to keep the conversation running fluently. Secondly, most of these students do not recognize the types of conversation strategies, let alone to use them in a con-versation. The main purpose of this study is to describe and identify conversation strategies employed by the fourth semester students of the English Department of Tadulako University in English conver-sations to maintain the conversation running fluently. The design of this study was qualitative. Twenty-four students taking Conversation Course IV at the English Department of Tadulako University were the subjects of the study. Twelve conversation strategies were discovered: (1) filler, (2) asking for clarification, (3) code switching, (4)  interpretive summary, (5) changing topic, (6) circumlocution (7) comprehension check, and (8) self-correcting, plus four other types of conversation strategies that are not listed in communication theories: (9) giving clarification, (10) correcting other, (11) self-referencing, and (12) surprising, and seven non-verbal conversation strategies in maintaining conver-sation taking place well: (1) shake-hands, (2) thumb-up, (3) open palm,  (4) smile, (5) eye contact, (6) head nodding, and (7) head shaking. In conclusion, conversation strategies can help the students get some useful feedback from each other on their own performances. They can prepare students to be ready participating in English conversation activities, and they simultaneously help students overcome the conversation problems of insufficient linguistic knowledge of the target language.  Key Words: conversation, conversation strategies, communicative competence